Biofuels, promise or fallacy (2012)
By stoichiometric relationships between products and reactants in the balanced reaction equations and considering the heat of combustion of six pure compounds used in first approximation as representative of gas, alcohol, liquefied petroleum gas (LPG), gasoline, diesel and biodiesel, it was demonstrated that, unlike other fuels, biofuels, alcohol and biodiesel, in their combustions produce more pollution, generate less energy per unit mass and consume less oxygen. That gave arguments that dispute the actual apology regarding the advisability of using them as substitutes for fossil fuels.